Penerapan Metode Pembelajaran Computational Thinking (CT) pada Anak Usia Dini untuk Kemampuan Bahasa - Sumiyati Sumiyati; Eka Danik Prahastiwi (MASALIQ, 2026)
The application of the Computational Thinking (CT) learning method in early childhood education (PAUD) has become an important focus in strengthening children’s cognitive skills and language abilities. This study aims to examine the implementation of the CT method in early childhood and its influence on children’s language development. This study used a qualitative approach with a case study design conducted in a Playgroup (KB) in Pacitan Regency. Data were collected through structured observation, in-depth interviews with teachers and parents, and documentation of children’s learning activities. The results showed that the application of CT through sequencing, pattern recognition, decomposition, and algorithmic thinking activities contributed to improving children’s active vocabulary, narrative ability, and verbal communication skills. This study concludes that the integration of CT into early childhood learning is effective in stimulating language development in an enjoyable and contextual manner. The implications of this study emphasize the importance of developing innovative CT-based learning methods in PAUD, while also opening opportunities for further research with a broader sample scope and more diverse combinations of digital media.